Trace Metal Contamination in Soils and Waters around the Abandoned Colliery Site of Bagworth Heath, English Midlands - Hawrami, Karzan Karzan Abdullah Mohammed Hawrami (Iraqi Journal of Science, 2019)
Abandoned mines and mining activities are considered one of the most significant sources of trace metal contamination worldwide. Those activities resulted in environmental contamination of particular surrounding ecosystems of abandoned ecosystems. The main aim of this study is to evaluate the trace metal contamination in the vicinity of abandoned mine located in Leicestershire English Midland. Twelve soil samples with two water samples were collected from the abandoned mine site. Test results showed a wide range of soil pH was observed from extremely acid (2.5) to slightly alkaline (7.4) as well as LOI from 8% organic matter content to 40% was found. Moreover, results demonstrated that most elements were below Soil Guideline Values (SGV) including As, Cd, pb and Ni, while the high total concentration was found for the case of (Al and Fe). In addition, a high concentration of Al and As were found in water samples in both pipe and pond water while other investigated metals were found in slightly higher than permissible limits of (10, 3,10, 20 ) respectively. According to this study Al was the dominant heavy metals in the area followed by the Fe>Ti>Ba>Mn>V>Rb>Sr>Zn>Cr>Cu> Ni> As>Pb> Co>Cs> Mo>Se>U>Cd.